THE MESOPROTEROZOIC BASEMENT IN THE SOUTHERN BALTIC SEA: INSIGHTS FROM THE G 14-1 OFF-SHORE BOREHOLE - Obst K.; Hammer J.; Katzung G.; Korich D. (My University, 2004)
The continuation of the Mesoproterozoic basement of the southern Fennoscandian Shield is documented in the G 14–1 off-shore borehole, northeast of the island of Rgen, where crystalline rocks of monzogranitic composition occur beneath flat-lying early Palaeozoic sediments at a depth of approximately 2,000m. The greenish-grey, or partly reddish-grey, granites show a slightly porphyritic texture marked by plagioclase crystals or aggregates in a groundmass dominated by fresh microcline. Chloritized biotite occurs as a subordinate mafic phase. Ductile and brittle deformation is indicated by a weak foliation and the occurrence of several cataclastic zones, respectively. Major and trace element geochemistry suggest that these rocks are K-rich calc-alkaline granites and represent a restite-poor melting product of a granodioritic protolith. The low MgO, Cr, Ni and Co concentrations and relatively high content of accessory phases (apatite, zircon) point to formation of water undersaturated, high temperature (>900C) melts at low degrees of partial melting. Although the G 14 granite lacks hornblende, in contrast to most of the granites from Bornholm, it seems geochemically related to them. Analysed samples mostly fit an intermediate position between the Rnne and Vang granitoids, which both belong to a group of Mesoproterozoic intrusions showing partial ductile deformation. (Y+Nb) vs. Rb plots suggest that all these granitic rocks were generated in intracratonic conditions. A genetic relationship between them and contemporaneously intruded Karlshamn-group granites in Blekinge, eastern Scania and Smland is supported by intrusion age of 1,4603Ma obtained from Pb-Pb isotope ratios measured on single zircons of the G 14 granite.
Keywords: Mesoproterozoic; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская